2014
DOI: 10.1063/1.4858969
|View full text |Cite
|
Sign up to set email alerts
|

Near-field mapping of Fano resonances in all-dielectric oligomers

Abstract: We demonstrate experimentally Fano resonances in all-dielectric oligomers clusters of dielectric particles. We study two structures consisting of a ring of six ceramic spheres with and without a central particle and demonstrate that both structures exhibit resonant suppression of the forward scattering associated with the Fano resonance originated from the excitation of magnetic dipole modes. By employing the near-field measurement techniques, we establish the relation between near- and far-field properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 29 publications
0
46
0
Order By: Relevance
“…[52] the existence of the Fano resonances in dielectric oligomers has been demonstrated for the first time. Due to the scalability of Maxwell equations, the authors used microwave ceramic spheres with sizes of several centimeters (instead of Si nanoparticles).…”
Section: B Fano Resonances In All-dielectric Oligomersmentioning
confidence: 98%
See 2 more Smart Citations
“…[52] the existence of the Fano resonances in dielectric oligomers has been demonstrated for the first time. Due to the scalability of Maxwell equations, the authors used microwave ceramic spheres with sizes of several centimeters (instead of Si nanoparticles).…”
Section: B Fano Resonances In All-dielectric Oligomersmentioning
confidence: 98%
“…Recently, it was shown that the oligomers composed of high-index dielectric nanoparticles are also able to exhibit the Fano resonance [50][51][52][128][129][130][131]. The important feature of such dielectric oligomers, comparing to their metallic counterparts, is the localization of the electromagnetic field inside the dielectric nanoparticles.…”
Section: B Fano Resonances In All-dielectric Oligomersmentioning
confidence: 99%
See 1 more Smart Citation
“…So, absorption in metal nanoparticles decreases the efficiency of the EIT and Fano resonances. To reduce the losses, researchers have reported that the use of silicon-based dielectric nanostructures like oligomers [30][31][32] and nanorod arrays [33] produces EIT and Fano resonances with large Q-factors that reach to several hundreds or even higher [34,35]. Therefore, the use of high refractive index dielectric nanostructures is a perfect option to produce EIT and Fano resonances with high Q-factors, which make them promising for low loss slow-light devices and biosensing applications.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, because of the negative effects by the diffraction limit and their subradiant nature, the Bmagnetic resonances^will find a new path for waveguiding applications and light focusing [6]. In fact, the promotion of coil-type modes [7] plays an important role in the generation of the Bmagnetic modes.^Therefore, many nanostructures have been designed such as the three gold disks [8], double split-ring resonator [9], and metallic oligomers [10]. In the past few years, the electric Fano resonances [11][12][13][14][15][16][17][18], which result from the coupling between the dark (or subradiant) electric modes and the bright (or superradiant) modes, have been investigated extensively due to their promising applications in the field of Fano switch [19], second harmonic generation [20], filtering or color sorting [21], and substrate for surface enhanced Raman spectroscopy [22].…”
Section: Introductionmentioning
confidence: 99%